Volume 5: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30330
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reynolds Number, Compressibility and Free Stream Turbulence on Profile Entropy Generation Rate

Abstract: Detailed aerodynamic data from the suction surface boundary layer on a turbine blade arranged in a linear subsonic cascade was acquired under high free stream turbulence conditions (∼ 5.2%) generated using a perforated plate placed upstream of the cascade. In addition, data was also obtained from a transonic turbine cascade utilizing the same blade profile but of much smaller chord at free stream turbulence levels of 3.5%. Velocity profiles from the laminar, transitional and turbulent boundary layers were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Further, few experiments have had sufficient measurements to calculate the entropy generation. Some at the University of Limerick have previously predicted and measured the local entropy generation rate within transitional boundary layers with streamwise pressure gradients (Walsh et al [18] and Griffin et al [19]).…”
Section: Related Literaturementioning
confidence: 99%
“…Further, few experiments have had sufficient measurements to calculate the entropy generation. Some at the University of Limerick have previously predicted and measured the local entropy generation rate within transitional boundary layers with streamwise pressure gradients (Walsh et al [18] and Griffin et al [19]).…”
Section: Related Literaturementioning
confidence: 99%
“…Loss generation can be studied using the entropy generation rate concept, as done by Griffin et al [2] for a turbine profile boundary layer or the mean flow kinetic energy dissipation rate, introduced by Moore et al [3] for secondary flows in turbine cascades. For adiabatic flows the mean kinetic energy dissipation rate and the entropy generation rate are two faces of the same loss generation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In these types of separated flows the separation location and its extent would be highly dependent on the turbulence intensity and Reynolds number. Griffin et al (2002) showed that increasing free-stream turbulence intensity moves the transition location upstream while, simultaneously, the chordwise length of the transition region is reduced due to a change in the transition mechanism from the natural to the bypass mode. Also, they demonstrated that increasing the Reynolds number will also move the transition point upstream, but found that the length of the transition region is almost independent of the Reynolds number.…”
Section: Introductionmentioning
confidence: 99%